Effects of Local Application of Hyaluronic Acid on Postoperative Sequelae after Surgical Removal of Impacted Lower Third Molars - Imad Sadiq Marouf; Atalla F. Rejab (University of Mosul, College of Dentistry, 2020)
Aims: The aims of the current research is to estimate the effectiveness local application of hyaluronic acid (HA) gel on pain, facial swelling, and trismus after extraction of impacted mandibular third molars. Materials and Methods: The research included a total of 44 healthy patients between the ages of 18-29 years with asymptomatic impacted lower third molars at time of extraction. Patients were randomly divided into two groups; 0.8% HA was applied to the HA group (n=22) while nothing was applied in the control group (n=22). Patients' pain levels were assessed at the first, third and seventh postoperative days and the pain scored on a numerical rating scale (NRS). Results: Pain score, facial swelling and trismus were highest on the first postoperative day and decreased gradually in both Control and HA group on the 3rd and 7th postoperative days. There were statistically significant differences in Pain scores between Control and HA groups on the three postoperative days. However, for swelling the difference between the two groups was significant just on the 1st and 3rd postoperative days. There were no significant differences between the two groups regarding trismus over the days of review. Conclusions: The results of this study showed that after surgical removal of impacted teeth HA can produce an analgesic effect and therefore it may have a clinical benefit in reducing postoperative pain and facial swelling.